Examining students' clinical skills: Assessment of the 'unseen' client in a speech and language therapy clinic - Mc Tiernan, Kathleen; Walsh, Irene; Leahy, Margaret (AISHE, 2007)
Towards the end of their undergraduate careers, speech and language therapy stu- dents are expected to have developed an advanced level of clinical expertise, in the assessment, diagnosis and management of a wide range of communication disorders in children and adults. At the beginning of their final 30-day block placement, students have completed approximately 400 hours of supervised clinical work, and they are in the final stages of acquiring the knowledge and skills necessary to become practitioner scientists.
Case Studies of Good Practices in Assessment of Student Learning in Higher Education
PUBLISHED
Dublin
Keywords: Education; speech and language therapy clinic; Identities in Transformation; Education